KARAKTERISTIK MIKROBIOLOGI, KIMIA, DAN SENSORIS, SOSIS AYAM DENGAN PENAMBAHAN KHITOSAN DAN ANGKAK YANG DISIMPAN PADA REFRIGERATOR - , NIA VERGIYANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was conducted to study the effect of chitosan and anka rice addition as antibacterial agent on microbiology, chemical, and sensory characteristics of chicken sausage up to 21d of storage in the refrigerator. The ratio of addition anka rice 0:0,5:1:1,5:2% (w/w) and chitosan 0:0,5:1:1,5:2% (w/v) by dissolved chitosan on 1% acetic acid. Length of storage up to 21d in the refrigerator with observed 0, 7, 14, and 21d. The observed variables were antibacterial activity, microbiology (Enterobacteriaceae and Salmonella), chemical (moisture, protein, fat content and antioxidant activity), and sensory characteristics (color, flavor, taste, texture, and acceptability). Data of antibacterial activity were analyzed with Randomized Completely Block Design (RCBD), Enterobacteriaceae with One-Way ANOVA, the chemical and microbilogy data were analyzed using variance analysis of factorial pattern (4 length of storage Ã 5 concentration of chitosan and anka rice) followed by Duncanâs Multiple range Test (DMRT). The sensory characteristic data were analyzed using Kruskal-Walls Hedonic test, followed by Quantitive Descriptive Analysis (QDA) in model of spider web. Each treatment was consisted of three replications. Chitosan and anka rice addition up to 2% increased antioxidant activity, chitosan antibacterial, colour, taste, texture, acceptability respectively 1.92%, 3.06mm, 6.02, 0.58, 1.49, dan 1.34, but decreased moisture 2.54%. Length of storage of sausage up to 21 in the refrigerator increased antioxidant activity and flavour respectively 6.25% and 0.37, however decreased sausage texture 0.64. Chitosan:anka rice addition and length of storage up to 21d did not change protein content and fat. Enterobacteriaceae was detected on 21d but the population still very low, Salmonella was not detected population up to 21d. Based on the result it could be concluded, length of storage of chicken sausage in the refrigerator up to 21d still suitable for consumption.